1. The problem statement, all variables and given/known data I need to proof that VxU=(determinant) starting from VxU=|V||U|sinαe 2. Relevant equations VxU=|V||U|sinαe and what I'm aiming to is VxU=(uy⋅uz - uz⋅vy)i - (ux⋅vz - uz⋅vx)j + (ux⋅vy - uy⋅vx)k 3. The attempt at a solution U x V = |U||V|Sinαe (U x V)^2 = |U|^2|V|^2 cos^2α - 1 e (U x V)^2 = |U|^2|V|^2 cos^2α - |U|^2|V|^2 U x V = (ux + uy + uz) (vx + vy + vz)cos^2α - (ux + uy + uz) (vx + vy + vz) e This is where I get stuck. Can someone point me on the right direction? that cosine and e are disorienting me. Thanks.